KEMAMPUAN MANAJERIAL KEPALA SEKOLAH DALAM MENINGKATKAN PRODUKTIVITAS KERJA GURU TK PAUD TERPADU PONTIANAK - Haryanengsi, Haryanengsi; Yani T, Ahmad; Syahrudin, Husni (Universitas Tanjungpura, 2026)
This study aims to analyze the managerial ability of school principals in enhancing teacher productivity at TK PAUD Terpadu Pontianak. The research employs a qualitative descriptive method with a case study approach. The participants consist of 10 individuals: one principal (female, 59 years old, bachelor